PEMASARAN KOTA SEBAGAI PENDEKATAN DALAM PERENCANAAN RUANG KOTA - Prihantoro, Feri (VITASPHERE, 2012)
City marketing is a strategy to achieve city s vision, it should be supported with city planning as a foundation for city to create image, attraction, sufficient infrastructure, and human resources which support city marketing. City planning ;s not only to supply the citizen, but it is also to satisfy market target. In Indonesia, city planning process refers to guidance which is produced by central government. This situation makes city planning product is "similar" among cities and it is just supply oriented to citizen need with national standard. Even though, the purpose of the guidance is to facilitate local government to produce comprehensive city planning. Competitive advantage ;s an important strategy in city marketing. Unfortunately, because of the similarity of city planning, city has no competitive advantage. City has not attraction place which consists of economy attraction, quality of life, and also sufficient infrastructure. Place attraction is required in city marketing. It is necessary for city which uses city marketing approach in city planning with orientation to market target. Human resources with capacity in entrepreneurship are also important to produce city planning which has orientation in city marketing.